Sustainable gastronomy: a study of catering facilities-traditional farms in rural Vojvodina (R. Serbia) - Kalenjuk Pivarski, Bojana; Đerčan, Bojan; Šmugović, Stefan; Ivnović, Velibor (Eastern European Countryside, 2025)
Sustainable gastronomy is vital for the social, economic, and environmental development of every economic-tourist region. It has been extensively studied, providing insights into current management practices and potential future activities concerning the gastronomic offer and heritage in the hospitality industry. Vojvodina, located in the north of the Republic of Serbia, is an important multicultural region characterised by a blend of gastronomic influences from its current inhabitants and those who have historically shaped its identity. The fertile plains, combined with its culinary heritage, have made this region one of the most significant economic-tourist areas today, attracting visitors due to its unique gastronomic offerings. This study analysed ten catering farms using a specifically designed GastroFarm Model, which incorporates defined subindicators of the environmental, social, and economic dimensions. An overview of the results is presented in a ternary diagram. The study revealed a significant dominance of the economic-social dimension in the management practices of the farms studied, providing insights into aspects clearly visible to consumers (the traditional offerings and ethnic dishes.